1962
DOI: 10.1152/ajplegacy.1962.202.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on membrane potentials of lobster giant axon

Abstract: In the range 2–20 C, the resting potential of the lobster axon shows a greater increase with increase of temperature than can be explained by the Nernst relationship. Action potential also shows an initial increase with temperature, peaks at about 16 C, then decreases. Maximum rates of rise and fall of the action potential increase with temperature increase; duration of the propagated action potential decreases. Afterpotentials in this preparation are in the form of a delayed repolarization; as temperature is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

1963
1963
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…If the temperature was increased above 25°C, the resting potential did not increase very much, and began to decrease at temperatures higher than 300 C. Irreversible damage seemed to occur to the fibre at temperatures above 360 C. In agreement with previous plots of resting potential versus temperature for several preparations including the present one (e.g. Dalton & Hendrix, 1962;Spyropoulos, 1966;Hinke & McLaughlin, 1967), Fig. 3 shows a case where the dependence is not linear, being steeper in the lower temperature range.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…If the temperature was increased above 25°C, the resting potential did not increase very much, and began to decrease at temperatures higher than 300 C. Irreversible damage seemed to occur to the fibre at temperatures above 360 C. In agreement with previous plots of resting potential versus temperature for several preparations including the present one (e.g. Dalton & Hendrix, 1962;Spyropoulos, 1966;Hinke & McLaughlin, 1967), Fig. 3 shows a case where the dependence is not linear, being steeper in the lower temperature range.…”
Section: Resultssupporting
confidence: 92%
“…JORGE FISCHBARG Dalton & Hendrix, 1962;Spyropoulos, 1966;Hinke & McLaughlin, 1967), Fig. 3 shows a case where the dependence is not linear, being steeper in the lower temperature range.…”
mentioning
confidence: 96%
“…Photodynamic processes do not seem to be highly temperature dependent (Spikes & Livingston, 1969), and increases in temperature raise the resting potential and decrease spike duration (Dalton & Hendrix, 1962). Both of these effects are in the opposite direction to the results obtained here.…”
Section: Are Photodynamic Effects Reversible ?contrasting
confidence: 72%
“…It is suggested that there is a tem perature-dependent fraction of the resting potential in lobster axons which is either not present or inactive in the squid axon, where the resting potential remains constant between 3 and 20°C. In the lobster axon within the same range, the resting potential increases from 72 to nearly 82 mv (40).…”
Section: Stampflimentioning
confidence: 92%